2023
DOI: 10.1002/acn3.51774
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study to explore the effect of udenafil on cerebral hemodynamics in older adults

Abstract: Objective Phosphodiesterase‐5 inhibitors (PDE5Is) enhance vasodilation. We investigated the effects of PDE5I on cerebral hemodynamics during cognitive tasks using functional near‐infrared spectroscopy (fNIRS). Methods This study used a crossover design. Twelve cognitively healthy men participants (mean age, 59 ± 3 years; range, 55–65 years) were recruited and randomly assigned to the experimental or control arm, then the experimental and control arm were exchanged after 1 week. Udenafil 100 mg was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…This may have been brought to light by the MR study design, which estimates a lifetime risk due to inherited differences in PDE5 inhibition compared to shorter-term use following diagnosis of ED or PAH. How relevant this is to pharmacological PDE5 inhibition compared its genetic proxy requires further investigation, but the aforementioned RCT showing negative effects on verbal fluency, memory tests, and prefrontal cortex activation suggests validity to the concerns highlighted in this study (38).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This may have been brought to light by the MR study design, which estimates a lifetime risk due to inherited differences in PDE5 inhibition compared to shorter-term use following diagnosis of ED or PAH. How relevant this is to pharmacological PDE5 inhibition compared its genetic proxy requires further investigation, but the aforementioned RCT showing negative effects on verbal fluency, memory tests, and prefrontal cortex activation suggests validity to the concerns highlighted in this study (38).…”
Section: Discussionmentioning
confidence: 67%
“…However, the PASTIS randomised controlled trial (RCT) did not show a difference in cerebral blood flow with taldafil compared to placebo in older people with symptomatic small vessel disease, a patient population at high risk for the development of VaD (37). Similarly, another RCT found that PDE5 inhibition had no positive effect on behavioural outcomes, along with negative effects on cerebral haemodynamics (38). Sustained PDE5 inhibition may counterintuitively reduce cAMP levels due to activation of PDE2 from chronically increased cGMP concentration, resulting in the harmful effects seen in those with genetic variants mimicking PDE5 inhibition (39).…”
Section: Discussionmentioning
confidence: 99%